2012
DOI: 10.9771/2317-1219rf.v0i20.4612
|View full text |Cite
|
Sign up to set email alerts
|

A bioética na formação do biólogo: um desafio contemporâneo

Abstract: Avanços tecnocientíficos atuais levam a indagações sobre a postura a ser adotada pelos profissionais das ciências, tornando relevante a reflexão quanto à formação ética do biólogo. Neste contexto, o estudo teve como principal objetivo apresentar o panorama de inserção curricular da Bioética e disciplinas similares nos cursos de Graduação em Ciências Biológicas das Instituições Federais do Brasil. Almejou-se analisar também as linhas teóricas que fundamentam o ensino e as temáticas que predominam nesta abordage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…The hypothesis to be tested was that the contact helps the sensitization of this age group in relation to the social and environmental responsibilities that will involve their daily life in adulthood, allowing them to become protagonists, actively acting as professionals and citizens for the construction of a more fraternal and fair society. This assumption is in line with the analysis of students' perceptions about bioethics training at undergraduate and graduate levels [14][15][16][17][18][19][20][21][22][23][24][25][26][27] , which highlight the importance of stimulating critical thinking and the incorporation of ethical attitudes, which will be the basis for the teaching of principles, concepts and norms associated with bioethics [30][31][32][33][34] .…”
Section: Path Of Dialogue: a Bioethics Experience In Primary Schoolmentioning
confidence: 78%
See 2 more Smart Citations
“…The hypothesis to be tested was that the contact helps the sensitization of this age group in relation to the social and environmental responsibilities that will involve their daily life in adulthood, allowing them to become protagonists, actively acting as professionals and citizens for the construction of a more fraternal and fair society. This assumption is in line with the analysis of students' perceptions about bioethics training at undergraduate and graduate levels [14][15][16][17][18][19][20][21][22][23][24][25][26][27] , which highlight the importance of stimulating critical thinking and the incorporation of ethical attitudes, which will be the basis for the teaching of principles, concepts and norms associated with bioethics [30][31][32][33][34] .…”
Section: Path Of Dialogue: a Bioethics Experience In Primary Schoolmentioning
confidence: 78%
“…It is necessary that the teacher knows how to deal with the themes, values, rights, limits and respect, as well as the technological and scientific aspects that generate bioethical issues, and there is no specific training profile for this. Of particular note are the science and biology teachers, whose formative content is directly related to the first stages of the development of bioethics 20 . It is important to emphasize, however, if most of these contents are based on technocratic paradigms from the 1950s, aimed at preparing learners for decision-making, based on cognitive aspects, to the detriment of morals.…”
Section: Analysis and Discussion Of The Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…With the inclusion of bioethics subjects in biological and biomedical courses, the debate on animal use could begin. However, despite these early efforts, a recent study investigating the curricular integration of bioethics and similar learning opportunities in undergraduate biology programs at Brazilian federal institutions found that of 36 programs, only 19 (53%) included bioethics or similar courses for biology degrees (Dória and Moreira, 2011). Furthermore, increased emphasis on bioethics is strongly linked to medical practice, for example, the choice of subjects of study and the academic and professional trajectory of researchers (Diniz and Guilherm, 2002).…”
Section: History Of Brazilian Humane Educationmentioning
confidence: 99%
“…No ensino, a Bioética abre caminhos para discussões críticas e análises que ajudam a discernir o que é bom e correto com base nos valores morais vigentes na sociedade contemporânea (Dória, 2011). A Bioética enquanto disciplina dispõe uma caixa de ferramentas para auxiliar os sujeitos na discussão de dilemas e na resolução de conflitos éticos (Schramm, 2002), tornando-se desta forma importante para qualquer área de formação.…”
Section: Introductionunclassified